METHODS OF DEVELOPING STRENGTH QUALITIES OF YOUNG VOLLEYBALL PLAYERS - Juraboyev M. M. (Proximus Journal Publishing, 2024)
This article provides basic information about sample exercises, types of strength, the order of strength work and the main means of developing strength qualities in young volleyball players.
Keywords: Strength; static; isometric; myometric